2016
DOI: 10.1136/tobaccocontrol-2015-052771
|View full text |Cite
|
Sign up to set email alerts
|

Two-year trends and predictors of e-cigarette use in 27 European Union member states

Abstract: ObjectiveThis study assessed changes in levels of ever use, perceptions of harm from e-cigarettes and sociodemographic correlates of use among European Union (EU) adults during 2012–2014, as well as determinants of current use in 2014.MethodsWe analysed data from the 2012 (n=26 751) and 2014 (n=26 792) waves of the adult Special Eurobarometer for Tobacco survey. Point prevalence of current and ever use was calculated and logistic regression assessed correlates of current use and changes in ever use, and percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
148
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(165 citation statements)
references
References 20 publications
9
148
2
6
Order By: Relevance
“…Recent longitudinal studies show that e-cigarette use in adolescents is associated with higher smoking initiation rates 41–43. During the studied period, the use of e-cigarettes increased and the magnitude of this increase varied by country 44. We do not have reason to believe that the increase was smaller in countries with PoS display bans than in those without, but there is a potential for some residual confounding.…”
Section: Discussionmentioning
confidence: 88%
“…Recent longitudinal studies show that e-cigarette use in adolescents is associated with higher smoking initiation rates 41–43. During the studied period, the use of e-cigarettes increased and the magnitude of this increase varied by country 44. We do not have reason to believe that the increase was smaller in countries with PoS display bans than in those without, but there is a potential for some residual confounding.…”
Section: Discussionmentioning
confidence: 88%
“…A previous study showed that adolescents who first tried to use e-cigarettes because they were cheap, because they wanted nicotine, or because they wanted to quit smoking tended to continue using e-cigarettes [19]. Additionally, adults who tried e-cigarettes for goal-oriented reasons (e.g., to use e-cigarettes where smoking was not allowed or to quit) were more likely to report continued use [30,31]. In our study, many e-cigarette users replied that they used e-cigarettes for the cessation of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014 prevalence of ever and current e-cigarette users was among US adults 12.6% and 3.7%, respectively (Schoenborn and Gindi, 2015). Among Europeans prevalence of ever users was 7.2% in 2012 and 11.6% in 2014, whereas prevalence of current users was 1.8% in 2014 (Filippidis et al, 2017). In Italy in 2013 ever e-cigarettes use was 6.8% (about 3.5 million Italians aged ≥15 years), and current e-cigarette use was 1.2% (about 600,000 Italians) (Gallus et al, 2014).…”
Section: Introductionmentioning
confidence: 99%